Evaluation of Water Residence Time, Submarine Groundwater Discharge, and Maximum New Production Supported by Groundwater Borne Nutrients in a Coastal Upwelling Shelf System. Issue 1 (29th January 2018) - Luo, Xin; Jiao, Jiu Jimmy; Liu, Yi; Zhang, Xiaolang; Liang, Wenzhao; Tang, Danling
Abstract: The biogeochemical processes in the continental shelf systems are usually extensively influenced by coastal upwelling and submarine groundwater discharge (SGD). Using eastern Hainan upwelling shelf system as an example, this study fully investigates SGD and coastal upwelling and their effects on the coastal nutrient loadings to the mixing layer of eastern Hainan shelf. Based on the spatial distributions of 223 Ra and 228 Ra, water residence time is estimated to be 16.9 ± 8.9 days. Based on the mass balance models of 226 Ra and 228 Ra, the total SGD of the eastern Hainan shelf is estimated to be 0.8 × 10 8 and 1.4 × 10 8 m 3 d −1, respectively. The groundwater borne dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphate (DIP) are estimated to be up to 1121.8 and 20.4 μ M m 2 d −1 . The coastal upwelling delivers 2741.8 μ M m 2 d −1 DIN and 217.7 μ M m 2 d −1 DIP into the mixing layer, which are predominant in all the exogenous nutrient inputs. The groundwater borne DIN will support a maximum new production of 7.5 m M C m 2 d −1, about up to 24.0% of the total new production in the study area. SGD‐derived nutrient could be significant as a missing DIN to support the new production in the mixing layer of eastern Hainan shelf. The findings contribute to a better understanding of biogeochemical processes under the influences of SGD and coastal upwelling in the study area and other similar coastal upwelling systems. Key Points: 226 Ra and 228 Ra are used to constrain water residence time and submarine groundwater discharge (SGD) in Hainan eastern upwelling (HEU) Groundwater borne nutrients and upwelling induced nutrients to the mixing layer are estimated in HEU SGD derived nutrient could be significant as a missing dissolved inorganic nitrogen to support the new production in HEU